Patient experience from a pilot study implementing software-based post-COVID case management in GP practices: a qualitative process evaluation - Sesterheim, Kathrin; Peters-Klimm, Frank; Baldauf, Annika; Ullrich, Charlotte; Merle, Uta; Szecsenyi, Joachim; Stengel, Sandra (Healthcare, 2025)
Background/Objectives: In Germany, the provision of healthcare for post-COVID patients primarily lies with general practitioners (GPs), who often lack the necessary knowledge and skills. As part of the PostCovidCare pilot study (PCC), case management software incorporating a symptom diary was introduced and piloted in n = 10 GP practices with n = 33 included patients involved (September 2022-March 2023). This study aimed to explore patients’ experiences. Methods: Semi-structured telephone interviews were transcribed and analyzed using qualitative content analysis. A total of n = 10 patient interviews were conducted (July-September 2023). Results: Patients’ experiences were heterogeneous. The service was largely structured, involving an extensive initial assessment, follow-up appointments, questionnaires, and support from medical assistants, but technical problems with the symptom diary occurred. The GP consultation played a prominent role. Positive aspects included being actively asked about their symptoms, being given a lot of time, initiating diagnostic and therapeutic measures, and having a closer relationship with their GP. Negative aspects included the time taken, resulting exhaustion, duplication of efforts, and insufficient involvement in the consultation process. Conclusions: The pilot study conducted at an early stage of the post-COVID era demonstrated the basic feasibility of case management in primary care from patients’ perspectives. In addition, for future projects, it is important to integrate patients into the design from the outset, adapt the software to users’ needs, and consider care providers’ perspectives.